The 2nd International Electronic Conference on Geosciences 2019
DOI: 10.3390/iecg2019-06208
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Vertical Accuracy for TanDEM-X 90 m DEMs in Plain, Moderate, and Rugged Terrain

Abstract: Synthetic Aperture Radar (SAR) interferometry technique generates digital elevation models (DEMs) and is used by various agencies widely. The recently released TanDEM-X DEM by DLR at 90 m spatial resolution is available for free download to users. This paper examines the accuracy of TanDEM-X DEM at different experimental sites with different topographic characteristics. Three sites were chosen, namely Kendrapara (Odisha), Jaipur (Rajasthan), and Dehradun (Uttarakhand) with plain, moderate, and highly undulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
3
6
1
Order By: Relevance
“…Recently, new freely available global-scale DEM products have been released, such as the TanDEM-X DEM [15], the Multi-Error-Removed Improved-Terrain (MERIT) DEM [21], the ALOS Global Digital Surface Model (AW3D30) [22], and the NASADEM [23]. Because these products are so new (TanDEM-X has been freely available since late 2018, MERIT 2017, AW3D30 and NASADEM since the beginning of 2020), fewer studies have evaluated their accuracy [24][25][26][27][28]. If their accuracy can be confirmed, these new DEM products, which are based on more current remote sensing data and better processing methods, will be highly valuable because of their ability to capture natural or man-made changes in the topography of terrestrial surfaces [29].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, new freely available global-scale DEM products have been released, such as the TanDEM-X DEM [15], the Multi-Error-Removed Improved-Terrain (MERIT) DEM [21], the ALOS Global Digital Surface Model (AW3D30) [22], and the NASADEM [23]. Because these products are so new (TanDEM-X has been freely available since late 2018, MERIT 2017, AW3D30 and NASADEM since the beginning of 2020), fewer studies have evaluated their accuracy [24][25][26][27][28]. If their accuracy can be confirmed, these new DEM products, which are based on more current remote sensing data and better processing methods, will be highly valuable because of their ability to capture natural or man-made changes in the topography of terrestrial surfaces [29].…”
Section: Introductionmentioning
confidence: 99%
“…The vertical accuracy of the 12 m TanDEM-X DEM product has been assessed using ICESat points [70], GPS ground truth values, and LiDAR observed values [76]-or a height error map (HEM) [77] for reference. However, to date, very few studies [78] have been conducted to assess the vertical accuracy of the TanDEM-X 90 m DEM and, particularly, its comparison with other freely available global DEMs [74,79,80].…”
Section: Tandem-x Demmentioning
confidence: 99%
“…The TerraSAR-X add-on for Digital Elevation Measurements (TanDEM-X) departs from an SRTM baseline and provides a new SAR-interferometry-based (synthetic-aperture radar) estimate of elevations globally (Wessel et al, 2018;Zink, 2014). TanDEM-X has been shown to be the most accurate global DEM in some land cover categories (bare, shrub-land, sparse vegetation and urban) (Hawker et al, 2019), and at the 95 % confidence level, Gesch (2018) finds that only TanDEM-X is suitable for delineating the LECZ below 10 m. Wessel et al (2018) found TanDEM-X to have biases in areas of rugged terrain, where there is heterogeneity in the landscape/land cover and elevation, and additional analyses have revealed that while TanDEM-X is highly accurate in flat to slightly undulating terrains, it tends to overestimate elevation when used in areas characterized by more sharply uneven terrain (Bhardwaj, 2019). Higher-resolution versions of TanDEM-X (0.4 and 1 arcsec) are available through proposal and a service fee for scientific use but were not utilized in this study.…”
Section: Tandem-x 90 Mmentioning
confidence: 99%
“…It deviates from the other population data sets in that it aims to measure ambient population -that is, population distribution averaged over a 24 h period, rather than census de jure measures linked to usual residence. LandScan Global is a 30 arcsec population surface which is not directly comparable year over year, since methodologies are updated with each release (Bright and Coleman, 2001;Bright et al, 2016;Rose and Bright, 2014;Mesev, 2003). Thus LandScan is not suitable for use as a time series.…”
Section: Landscanmentioning
confidence: 99%